Emergency department course of patients with asthma receiving initial emergency medical services care—Perspectives From the National Hospital Ambulatory Medical Care Survey - Alix Delamare Fauvel; Lauren T. Southerland; Ashish R. Panchal; Carlos A. Camargo Jr; Matthew L. Hansen; Henry E. Wang (Journal of the American College of Emergency Physicians Open)
Abstract Objective Although 911 calls for acute shortness of breath are common, the role of emergency medical services (EMS) in acute asthma care is unclear. We sought to characterize the demographics, course, and outcomes of adult emergency department (ED) patients with asthma in the United States receiving initial EMS care. Methods We analyzed data from the 2016–2019 National Hospital Ambulatory Medical Care Survey (NHAMCS). We included patients aged ≥18 years with an ED visit diagnosis of asthma, stratifying the cases according to initial EMS care. Accounting for the survey design of NHAMCS, we generated nationalized estimates of the number of EMS and non‐EMS asthma visits. Using logistic regression, we determined the associations between initial EMS care and patient demographics (age, sex, race, and insurance type), ED course (initial vital signs, triage category, testing, medications), and outcomes (hospital admission, ED length of stay). Results Of 435 million adult ED visits during 2016–2019, there were ≈5.3 million related to asthma (1.3 million annually, 1.2%; 95% confidence interval [CI], 1.1%–1.4%). A total of 602,569 (150,642 annually, 11.3%; 95% CI, 8.6%–14.8%) ED patients with asthma received initial EMS care. Compared with non‐EMS asthma patients, EMS asthma patients were more likely to present with an “urgent” ED triage category (odds ratio [OR], 22.2; 95% CI, 6.6–74.9) and to undergo laboratory (OR, 2.78; 95% CI, 1.41–5.46) or imaging tests (OR, 2.42; 95% CI, 1.21–4.83). ED patients with asthma receiving initial EMS care were almost 3 times more likely to be admitted to the hospital (OR, 2.81; 95% CI, 1.27–6.25). There were no differences in demographics, ED use of β‐agonists or corticosteroids, or ED length of stay between EMS and non‐EMS asthma patients. Conclusions Approximately 1 in 10 adult ED patients with asthma receive initial care by EMS. EMS asthma patients present to the ED with higher acuity, undergo more diagnostic testing in the ED, and are more likely to be admitted. Although limited in information regarding the prehospital course, these findings highlight the more severe illness of asthma patients transported by EMS and underscore the importance of EMS in emergency asthma care.